A pesquisa na prática docente de professores formadores: um estudo em um curso de licenciatura em matemática - Komatsu, Mirna Yshimine (2010)
The aim of this study was to understand how Trainer Teachers of a Degree in Mathematics, researchers in Mathematics Education link the research in their teaching practice. To achieve our aim we have proposed two questions, which guided this work: How the Trainer Teachers recognize/value the research in their teaching practice? What are the facilities and the difficulties found of Trainers Teachers in promoting to development research in its students, future teachers? We conducted interviews with trainer teachers of an Institution of Metropolitan area of São Paulo, which offers the Degree in Mathematics, and observed for two consecutive years in the event Jornada de Educação Matemática, sponsored by the institution. To understand the research in basic training, first discussed the concept of training and types of training, then present the concept of the reflective teacher, researcher teacher and the movements regarding to teachers research. In our analysis we found that trainer teachers recognize/value the research on the motivations that sent it to the master, with the knowledge and their ideas about the types of research that help the practice of the classroom. Also found facilities and difficulties in providing incentives for research, especially at work to guide the conclusion of course, Jornada de Educação Matemática and the disciplines of the course